2020
DOI: 10.1016/j.ypmed.2019.105903
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tobacco smoking and electronic cigarette use among adolescents in Italy: Global Youth Tobacco Surveys (GYTS), 2010, 2014, 2018

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 15 publications
0
20
2
2
Order By: Relevance
“…The latest prevalence of 14.8% was similar to the GYTS survey in the Philippines in 2015 21 . However, it is double the rate of 6.7% reported in Bangladesh 22 as well as 10%, 12.5% and 13.6% from surveys in Thailand 23 , Indonesia 24 , and 68 lower-income and middle-income countries 25 , respectively, although it is 5 percentage points lower than the study reported among youths in Italy 20 . Our study also found that current smoking was significantly higher among males compared to females (ratio 10:1).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The latest prevalence of 14.8% was similar to the GYTS survey in the Philippines in 2015 21 . However, it is double the rate of 6.7% reported in Bangladesh 22 as well as 10%, 12.5% and 13.6% from surveys in Thailand 23 , Indonesia 24 , and 68 lower-income and middle-income countries 25 , respectively, although it is 5 percentage points lower than the study reported among youths in Italy 20 . Our study also found that current smoking was significantly higher among males compared to females (ratio 10:1).…”
Section: Discussioncontrasting
confidence: 53%
“…Similar findings were reported by Miguel-Baquilod et al 18 among school-going adolescents in their surveys in 2000 and 2003. However, no similar pattern was observed in two waves of Global Youth Tobacco Survey (GYTS) among school-going adolescents in India 19 and in Italy 20 . The latest prevalence of 14.8% was similar to the GYTS survey in the Philippines in 2015 21 .…”
Section: Discussionmentioning
confidence: 94%
“…Although most of the participants consider cancer a serious disease, and one third are considered to be at high risk of developing cancer, the results of our study confirmed a wide diffusion of an unhealthy lifestyle among adolescents, that once consolidated during adolescence, may have substantial consequences in adulthood, including the risk of developing cancer. The consistently widespread smoking habit and alcohol consumption is worrying, although it is similar in respect to analogous surveys conducted in the adolescent populations [29] or those of higher ages [30][31][32][33]. Equally, or even more, concerning is the result on the poor physical activity and insufficient consumption of fruits or vegetables, although analogous to other reported frequencies in similar studies [31,33,34].…”
Section: Lifestyle Behaviors Related To Cancermentioning
confidence: 54%
“…Thus, it has been trying to reinvent itself by introducing a new portfolio of products, presenting itself as part of the solution to combat the tobacco epidemic, which it created in the first place. The strong marketing and promotional strategy of the tobacco industry has led to an increase in nicotine and tobacco product use among youth globally [ [4] , [5] , [6] , [7] , [8] , [9] , [10] ].…”
mentioning
confidence: 99%